2013
DOI: 10.1039/c3ob40236c
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of N-(4-sulfamoylphenyl)thioureas as Trypanosoma brucei leucyl-tRNA synthetase inhibitors

Abstract: Human African trypanosomiasis (HAT) is one of the most neglected diseases in the tropic regions, which is fatal if not treated in time. There is an urgent need for new therapeutics, especially those in new chemical classes. Leucyl-tRNA synthetase (LeuRS) has been paid much attention as a recently clinically validated antimicrobial target. Our group has previously reported T. brucei LeuRS (TbLeuRS) inhibitors, including benzoxaboroles targeting the editing site and pyrrolinones targeting the synthetic site. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Human foreskin fibroblasts (HFFs) were infected with tachyzoites of the virulent RH strain and treated with benzoxaboroles, pyrimethamine, the standard of care to treat toxoplasmosis, or vehicle (DMSO). We screened a group of 20 representative benzoxaboroles that were previously shown to have activity against bacteria, fungi or other eukaryotic parasites (Rock et al , ; Xia et al , ; Hernandez et al , ; Zhang et al , ; Palencia et al , ). Some of these compounds were known to target leucyl‐tRNA synthetase (LeuRS).…”
Section: Resultsmentioning
confidence: 99%
“…Human foreskin fibroblasts (HFFs) were infected with tachyzoites of the virulent RH strain and treated with benzoxaboroles, pyrimethamine, the standard of care to treat toxoplasmosis, or vehicle (DMSO). We screened a group of 20 representative benzoxaboroles that were previously shown to have activity against bacteria, fungi or other eukaryotic parasites (Rock et al , ; Xia et al , ; Hernandez et al , ; Zhang et al , ; Palencia et al , ). Some of these compounds were known to target leucyl‐tRNA synthetase (LeuRS).…”
Section: Resultsmentioning
confidence: 99%
“…More recently, a new class of T. brucei LeuRS inhibitors, N-(4-sulfamoylphenyl)thioureas, which targets the synthetic catalytic site, has been discovered through the screening and modification of a small, targeted library of putative aaRS inhibitors (Zhang et al, 2013). This class of inhibitors are designed to inhibit by mimicking the intermediate product, aminoacyl-AMP.…”
Section: Existing Aars Inhibitors In Parasitesmentioning
confidence: 99%
“…(2011) and Zhang et al (2013) investigated T. brucei LeuRS using a structure-based drug design approach [12,54]. …”
Section: Inhibitor Identification Using Structure-based Drug Designmentioning
confidence: 99%
“…By screening an in-house database of 500 compounds, Zhang et al [54] identified a T. brucei LeuRS inhibitor with an N -(4-sulfamoylphenyl)thiourea core structure (compound 22 , IC 50 = 174.5 μM; Figure 9). Computational studies suggested thiourea compounds bind to the synthetic active site rather than the editing active site.…”
Section: Inhibitor Identification Using Structure-based Drug Designmentioning
confidence: 99%